2002
DOI: 10.1007/s11664-002-0105-8
|View full text |Cite
|
Sign up to set email alerts
|

Intermetallic compounds formed during interfacial reactions between liquid Sn-8Zn-3Bi solders and Ni substrates

Abstract: The Sn-8Zn-3Bi (wt.%) solder was prepared by encapsulating pure Sn (99.9%), Zn (99.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8]. To avoid the excessive loss of solid metals in contact with the alloys during soldering, data on metal dissolution rates in molten solders are needed.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8]. To avoid the excessive loss of solid metals in contact with the alloys during soldering, data on metal dissolution rates in molten solders are needed.…”
Section: Introductionmentioning
confidence: 99%
“…No systematic investigations relevant to the phase equilibria and thermodynamic properties of the Ni-Sn-Zn ternary system have been published, although it was reported that Ni 3 Sn 4 has significant solubility of Zn. 17,19 Based on the constituent binary systems, 21-23 the thermodynamic database for the ternary system is thus extrapolated to calculate the scale factor I=I 0 for the heterogeneous nucleation rate of various phases at the Sn-Zn/Ni interfaces. Since c-Ni 5 Zn 21 has formed during the preparation of the Sn-Zn/Ni couples, the present calculations are thus only carried out for 673 K (Fig.…”
Section: Nucleation Kinetics Considerationmentioning
confidence: 99%
“…To date, numerous studies relevant to interfacial reactions between Sn-Zn solder alloys and metallic substrates such as Cu and Ni have been published. [11][12][13][14][15][16][17][18][19][20] Chan et al 18 studied liquid/ solid Sn-9wt.%Zn/Ni couples at soldering temperatures ranging from 250°C to 350°C. They observed c-Ni 5 Zn 21 formation at the interfaces and determined that its growth was diffusion controlled.…”
Section: Introductionmentioning
confidence: 99%
“…), see, for example, [1][2][3][4][5]. In Europe the extensive search for new lead-free soldering materials is now coordinated by COST Action MP0602 till 2011.…”
Section: Introductionmentioning
confidence: 99%